Food Security : Threats and Challenges of Sustainable Paddy Production in Sarawak - Rosita, Hamdan; Sharon, Hou Wan; Audrey, Liwan; Freddy Yeo Kuok, San; Nur Zaimah, Ubaidillah (2022)
Rice is a staple food in Malaysia, hence paddy farming is vital to Malaysian households. However, the total amount of local rice output is still insufficient to meet household demand. There are several areas in Sarawak that are excellent for agriculture, particularly paddy growing. To maximise productivity, this potential agricultural area had not yet been used to its full potential. This study aims to highlight the challenges and threats facing Sarawak's paddy cultivation. This study collects qualitative information and contrasts findings from Sarawak's rural and sub-urban paddy farming. Interviews with 30 farmers were done in the sub-urban areas of Lundu and Siburan as well as the rural production areas of Bario and Long Seridan. Thematic analysis has been used to analyse the data. The results show that threats to and challenges to the sustainable production of the paddy sector include subsidies, a lack of understanding of the enhancement programme, a lack of communication channels to inform about production issues, a lack of marketing channels for the products, and other problems like price, ageing factors, and others. In the study, some suggestions for improving the sector will be found.